2004
DOI: 10.1016/s0014-5793(04)00278-9
|View full text |Cite
|
Sign up to set email alerts
|

Slow ADP‐dependent acceleration of microtubule translocation produced by an axonemal dynein

Abstract: Dynein has four nucleotide binding sites, of which the functional signi¢cance is unknown except for the single catalytic site. To obtain clues to the function of non-catalytic nucleotide binding, we examined the e¡ect of ADP on the in vitro motility of Chlamydomonas inner-arm dynein species 'a'. Upon continuous perfusion with ATP and ADP, microtubules glided on a dynein-coated glass surface with a velocity that gradually increased over a few minutes. The velocity increased faster at higher ADP concentrations. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
33
1

Year Published

2007
2007
2009
2009

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 17 publications
5
33
1
Order By: Relevance
“…Without ADP preincubation, MTs did not show smooth unidirectional gliding but displayed irregular back-and-forth movements immediately after the introduction of MTs and ATP into the chamber. These observations suggest that OAD is activated by ADP through a slow process, similar to other kinds of dyneins studied previously (31,32). Thus, ADP regulation of in vitro dynein activity, first observed in inner arm dyneins (29), is a feature shared by Chlamydomonas OAD.…”
Section: Adp Incubation Of Oad Enhances and Stabilizes Mt Gliding-supporting
confidence: 79%
“…Without ADP preincubation, MTs did not show smooth unidirectional gliding but displayed irregular back-and-forth movements immediately after the introduction of MTs and ATP into the chamber. These observations suggest that OAD is activated by ADP through a slow process, similar to other kinds of dyneins studied previously (31,32). Thus, ADP regulation of in vitro dynein activity, first observed in inner arm dyneins (29), is a feature shared by Chlamydomonas OAD.…”
Section: Adp Incubation Of Oad Enhances and Stabilizes Mt Gliding-supporting
confidence: 79%
“…It has been demonstrated that ADP is involved in the regulation of flagellar motility and dynein activity (Kinoshita et al, 1995;Omoto et al, 1996;Yagi, 2000;Kikushima et al, 2004). Our study indicated that the presence of a very low concentration of ADP is essential for continuous beating at very low ATP concentrations.…”
Section: Introductionsupporting
confidence: 50%
“…ADP has been shown to be a factor enabling the non-motile Chlamydomonas flagella missing a part of the central pair or radial spokes to beat (Omoto et al, 1996). ADP also increases the velocity of microtubule sliding by isolated inner arm dynein (Yagi, 2000;Shiroguchi and Toyoshima, 2001;Kikushima et al, 2004). The motile activity of cytoplasmic dynein has been shown to be regulated by the condition of nucleotide binding (Kon et al, 2004).…”
Section: Importance Of Adp In Flagellar Oscillationmentioning
confidence: 99%
“…To further examine the effects of the fluorescent ATP and ADP analogues on the dynein motile activity, we studied the role of ADP which has been shown to increase the initial velocity of microtubule translocation at 0.1 mM ATP by inner arm dynein of Chlamydomonas attached to the glass surface [Kikushima et al, 2004]. We found a similar increase of the velocity of microtubule translocation in 21S dynein: at 1 mM ATP the mean velocity gradually increased over a range of *10 min (Fig.…”
Section: Effects Of Stable Binding Of Adp On the Motile Activity Of Dmentioning
confidence: 78%
“…These inhibitory effects of higher concentrations of ATP can be released by the presence of ADP [Kinoshita et al, 1995;Omoto et al, 1996]. The role of ADP that enhances the dynein motile activity has also been shown in microtubule gliding assay experiments of purified monomeric dynein [Yagi, 2000;Shiroguchi and Toyoshima, 2001;Kikushima et al, 2004] and in experiments in which mechanical bending induced beating in motionless demembranated flagella at very low ATP conditions [Ishikawa and Shingyoji, 2007]. These findings concerning the roles of ATP and ADP seem to be related to the structural uniqueness of the dynein molecule with its multiple nucleotide-binding sites.…”
Section: Introductionmentioning
confidence: 79%